2010
DOI: 10.1111/j.1469-0691.2009.02912.x
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumoniae bacteraemia in a region of Canada

Abstract: The second case of magA+ rmpA+ hypermucoviscosity phenotype Klebsiella pneumoniae infection was documented in Canada, in an immigrant from Algeria. To ascertain whether this represented recent importation of the strain or local transmission within Canada, a retrospective study of K. pneumoniae bacteraemia was conducted in the region, from 1997 to 2007, and 411 episodes were identified. No epidemiological evidence for local transmission of this strain was found. However, for the first time, the population incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Division of Microbiology, Calgary Laboratory Services; Departments of 2 Pathology & Laboratory Medicine; 3 Medicine; 4 Microbiology and Infectious Diseases; 5 Critical Care, University of Calgary, Calgary, Alberta Correspondence: Dr Daniel B Gregson, Calgary Laboratory Services, #9, 3535 Research Road Northwest, Calgary, Alberta T2L 2K8.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Division of Microbiology, Calgary Laboratory Services; Departments of 2 Pathology & Laboratory Medicine; 3 Medicine; 4 Microbiology and Infectious Diseases; 5 Critical Care, University of Calgary, Calgary, Alberta Correspondence: Dr Daniel B Gregson, Calgary Laboratory Services, #9, 3535 Research Road Northwest, Calgary, Alberta T2L 2K8.…”
mentioning
confidence: 99%
“…During the past decade, community-acquired infections due to hypermucoviscous K pneumoniae, consisting of primary liver abscess, meningitis and endophthalmitis, were first recognized in Southeast Asia. These phenotypes of K pneumoniae have also been associated with bacteremia (2) and pneumonia (3,4), especially in patients with comorbid conditions such as diabetes mellitus (1). Hypermucoviscous isolates of K pneumoniae appear to be common in Taiwan and South Africa (5) but rare in Western Europe and North America (5,6).…”
mentioning
confidence: 99%
“…A number of studies have identified co-morbidities most notably cancer and diabetes as risk factors for development of Klebsiella species BSI [1,14,[30][31][32][33][34]. However, with the exception of the population-based investigation reported by Meatherall et al, these studies have been within selected cohorts that are at significant potential risk for bias.…”
Section: Discussionmentioning
confidence: 99%
“…Population-based studies minimize a number of important biases and have been recognized as optimal designs to evaluate the epidemiology of BSIs [12]. However, to our knowledge only three previous studies have evaluated Klebsiella species BSI in non-selected populations [1,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation